Automatic Translation of Spatial and Non-Spatial Expressions from English into Portuguese: A Study Involving Qualitative Spatial Reasoning (Linguamática, 2025)
Neural models for Machine Translation have been proving significant advances in performance in recent years, becoming the most widely employed tools for that task. Nevertheless, they still struggle with semantically complex expressions. In this paper, we investigated the performance of two of the most widely used systems available today, namely Google Translator and DeepL, in translating expressions involving representing objects in physical space, always using the same prepositions in English, divided into situations admitting spatial interpretations or not. Formalizations based on Qualitative Spatial Reasoning models are applied to the representation of the spatialized expressions, making it possible to compare the logical form of spatial information in the original texts and in automatic translations from English into Portuguese.Results show that these two major translation systems still make many mistakes when it comes to relatively complex expressions. Among them, Google Translator had more errors globally (35.52%) whereas DeepL, with the best overall performance (11.72% of errors), made significantly more mistakes with expressions involving spatiality, which suggests that translating these expressions increases the difficulty of translation for this model. In addition, a study on the specific type of difficulties in spatialized expressions shows that the most frequent machine translation problem concerns the incorporation of manner into the predicate, which is realized by different means in English (where the verb tends to incorporate manner) and in Portuguese (where manner is realized in adjuncts to the verb). Results from the present work may provide specific criteria for evaluating and improving machine translation models between these and other languages in which the same differences in predication occur.
Keywords: neural machine translation; spatial semantics; qualitative spatial reasoning; English-Portuguese machine translation; polysemy; language typology